Effects of digital dewaxing methods on K-means-clusterized IR images collected on formalin-fixed paraffin-embedded samples of skin carcinoma - Sebiskveradze, D.; Gobinet, C.; Ly, E.; Manfait, M.; Jeannesson, P.; Herbin, M.; Piot, O.; Vrabie, V. (2008 8th IEEE International Symposium on BioInformatics and BioEngineering, 2008)
Mid-IR spectral imaging is an efficient method to analyze biological samples. Several research studies showed its potential to diagnose cancerous tissues. However, some limitations appear when formalin-fixed paraffin-embedded tissues are studied due to the intense IR contribution of paraffin, unless to perform a time-consuming and aggressive chemical dewaxing. We propose in this paper to analyze the efficiency of two digital dewaxing methods developed to remove the paraffin influence on IR images acquired on a cancerous skin sample. The first method is the extended multiplicative signal correction (EMSC), which is a preprocessing step applied to neutralize the IR contribution of paraffin. The second one, previously developed for Raman spectroscopy of paraffined tissues, is based on the independent component analysis (ICA) and the nonnegatively constrained least squares (NCLS). ICA+NCLS permits to remove the IR spectral signature from tissue spectra. Both preprocessing methods are compared on the basis of K-means-clusterized IR images in respect to a conventional histopathological staining. In conclusion, these preliminary results show the efficiency of the preprocessing methods; however ICA+NCLS has to be improved to get more relevant outcomes.